2017
DOI: 10.1590/1678-457x.09417
|View full text |Cite
|
Sign up to set email alerts
|

Study of the consumers of ready-to-drink juices and fruit nectars

Abstract: Juices and fruit nectars are an important segment of the beverage market in Brazil. The aim of this study was to analyze and characterize the profile of consumers of ready-to-drink juices and fruit nectars. A semi-structured questionnaire was applied to 389 patrons, intentionally and conveniently, when they approached the shelves. The chi-square test was applied to associate sociodemographic variables and consumption profile of the beverages with the type of establishment. Logistic regression models were devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…Moreover, nondairy beverages also have high sensory acceptability by consumers. Santos et al (2018) surveyed the preference of 389 consumers on different beverages. The study reported that consumers preferred fruit juices over soda beverages.…”
Section: Nondairy B E Ver Ag E S a S Prob Iotic C Arriermentioning
confidence: 99%
“…Moreover, nondairy beverages also have high sensory acceptability by consumers. Santos et al (2018) surveyed the preference of 389 consumers on different beverages. The study reported that consumers preferred fruit juices over soda beverages.…”
Section: Nondairy B E Ver Ag E S a S Prob Iotic C Arriermentioning
confidence: 99%
“…Minuman sari buah adalah produk pangan yang tanpa diolah lebih lanjut bisa dikonsumsi secara langsung karena dikemas secara khusus. Perkembangan global saat ini membuat perubahan gaya hidup sehingga konsumen lebih tertarik pada produk yang praktis (Santos et al, 2017). Industri pangan telah mengembangkan produk ke dalam karakteristik praktis untuk memenuhi kebutuhan konsumen.…”
Section: Pendahuluanunclassified
“…Some studies have demonstrated an increasement of the consumption of juices and fruit products in recent years, due to factors such as practicality, nutritional value and health concern, but there is still a shortage of fruit products in the market. However, due to the diversity of fruits in the country and cultural miscegenation, there is a demand for diversified flavors [4].…”
Section: Introductionmentioning
confidence: 99%